1994
DOI: 10.1093/jac/34.6.1051
|View full text |Cite
|
Sign up to set email alerts
|

Synergic inhibitory activity of amphotericin-B and γ interferon against intracellular Cryptococcus neoformans in murine macrophages

Abstract: Cryptococcus neoformans is responsible for pulmonary and meningal infections in HIV patients. The lack of effective cellular cooperation caused by the low level of CD4+ cells, and the resistance of C. neoformans to phagocytosis allows growth and persistence of the yeast in the host. We describe here an in-vitro model of intracellular replication of C. neoformans inside J774-A.1 macrophages, and the determination of the intracellular antifungal activity of amphotericin B and fluconazole alone or in association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 0 publications
4
21
1
Order By: Relevance
“…Our results indicating that AMB-induced NO production only in the presence of IFN-␥ as a costimulator are in accord with those obtained by several other authors in vitro (21,31,37) as well as in vivo (25). The dose of IFN-␥ necessary for costimulation of mouse peritoneal macrophages (20 IU ml) (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicating that AMB-induced NO production only in the presence of IFN-␥ as a costimulator are in accord with those obtained by several other authors in vitro (21,31,37) as well as in vivo (25). The dose of IFN-␥ necessary for costimulation of mouse peritoneal macrophages (20 IU ml) (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…These products have been shown to reinforce the antimicrobial activity of AMB by their cytotoxic effects (41,50,51). On the other hand, AMB has been found to induce nitric oxide (NO) production as a result of NO synthase (NOS) induction only in the presence of a costimulator such as gamma interferon (IFN-␥), lipopolysaccharide (LPS), and M-CSF (16,21,37). This NO production may also increase the antimicrobial activity of AMB (29,49).…”
mentioning
confidence: 99%
“…Previous work indicates that neither FLU nor AMB has activity against intracellular C. neoformans (24). From our set of lysosomotropic anticryptococcal drugs, we selected two agents known to accumulate within macrophages (amiodarone and thioridazine) and found that both were active against C. neoformans within J774 mouse phagocytes.…”
Section: Discussionmentioning
confidence: 99%
“…neoformans traffics to the phagolysosome of macrophages, replicates, and then escapes as part of its pathogenic life cycle in humans (23). Unfortunately, the two most widely used anticryptococcal drugs, AMB and FLU, do not appear to have activity toward intraphagocytic C. neoformans (24). Thus, molecules able to target C. neoformans within this important niche could serve as either useful stand-alone agents or, possibly, adjuvants to agents currently in use.…”
Section: Screen Of Prestwick Library Identifies Drug-like Molecules Withmentioning
confidence: 99%
See 1 more Smart Citation